Peran Kepala Madrasah serta Guru dalam Pengembangan Kurikulum Pendidikan Agama Islam - Mu'in, Bahrul; Ahid, Nur; Hamida, Itsna Melani (LPTK IAIN Kediri, 2023)
Science and innovation are continuously created to keep up with the times and the progress of human thought. Increased knowledge and innovation moreover encouraged for the advancement of human life. Developing the curriculum is carried out as a proactive step to provide answers to challenges that have grown from the progress of the times. This study uses a literature search method on the use of subjective strategies and socio-historical approaches that focus on important data about curriculum development. A teacher plays an irreplaceable role in curriculum development. The teacher carries out two main tasks, namely the task of delivering subjects and tasks related to the administration of lessons. In addition to teachers who have a strategic role in improving PAI education programs, the head of the madrasa as the head of the institution also has a very important contribution. Madrasah heads have a strategic role and high obligations, including in terms of curriculum development.